Nonlinear finite element analysis of integral bridge including foundation soil interaction (wrinkler analogy) - Md. Noh, Mohammad Soffi (2006)
Bridges without expansion joints are called "integral bridges." Eliminating joints from bridges crates concerns for the piles and the abutments of integral bridges because the abutments and the piles are subjected to temperature-induced lateral loads. This kind of bridges are becoming very popular due to different aspects such as good response under seismic loading, low initial costs, elimination of bearings, and less maintenance. However, the main issue related to the analysis of this type of structures is dealing with the soil-structure interaction of the abutment walls and the supporting piles. This study describes the implementation of a two dimensional finite element model of integral bridge system which explicitly incorporates the nonlinear soil response. The superstructure members have been represented by means of three-noded isoperimetric beam elements with three degree of freedom per node which take into account the effect of transverse shear deformation. The soil mass is idealized by eight noded isoperimetric quadrilateral element at near field and five noded isoperimetric infinite element to simulate the far field behavior of the soil media. The nonlinearity of the soil mass has been represented by using the Duncan and Chang approach. In order to study the behavior of integral bridge under varies loading condition including the effect of temperature load, three type of